THE EFFECT OF USING THE JARIMATIKA METHOD AND THE PYTHAGOREAN MULTIPLICATION TABLE ON SOLVING MATHEMATICAL CONCEPTS OF MULTIPLICATION OPERATIONS - Rini, Triana Sulistya; Nur Sofianto, Eko Wahyu; Irawati, Ratna Kartika (Waniambey: Journal of Islamic Education, 2025)
This study aims to determine the effect of students' numeracy skills by using the jaritmatika method and the Pythagorean multiplication table on student learning outcomes significantly in mathematics lessons on student multiplication operations. The method used in this research is the quasi experimental method of experimental research which is basically the same as cause-and-effect research but is carried out using pseudo-experimental methods. This research was conducted at SDN Sungai Jingah 5 with saturated sampling of grade III. The results showed that the numeracy skills of experimental grade students using the jaritmatika method and tables can be seen from the average results of 82.13 are in the "Very Good" qualification, while the numeracy skills of control grade students using the interactive discussion method 73.87 are in the "Good" qualification. Based on the calculation with the Independent Simple T Test "T Test" with asymp, Sig (2-tailed) is 0.041, because 0.041 <0.05 then H 0is rejected and H ais accepted so it can be concluded that there is a significant difference in the learning outcomes of the ability to count multiplication of the experimental grade (using the jaritmatika method and table) and the control grade (using interactive discussions). The implication of this research can be used as an alternative method of learning mathematics calculation for elementary school students.